Comparing perspectives on medication treatment for opioid use disorder between national samples of primary care trainee physicians and attending physicians. (1st November 2020) - Kennedy-Hendricks, Alene; Barry, Colleen L.; Stone, Elizabeth; Bachhuber, Marcus A.; McGinty, Emma E.
Highlights: Primary care physicians view opioid use disorder (OUD) medications as effective. Trainee physicians express greater interest in treating OUD than attendings. Trainee physicians more receptive to prescribing buprenorphine than attendings. Primary care physicians unwilling to live near OUD medication treatment providers. Mixed support for policies to loosen restrictions on OUD medication prescribing. Abstract: Background: Most people with opioid use disorder (OUD) are not treated with FDA-approved medications methadone, buprenorphine, or naltrexone. Expanding capacity for evidence-based OUD medication in primary care is a national priority. No studies have examined primary care trainee physicians' attitudes about these medications. This study surveyed a national sample of primary care trainee physicians and compared their views with those of primary care attending physicians (i.e., those who have completed training). Methods: Random samples of 1, 000 trainee physicians and 1, 000 attending physicians specializing in family, internal, or general medicine were selected from the American Medical Association Masterfile. Surveys were mailed February-August 2019. 45 % of eligible trainee physicians and 54 % of eligible attending physicians responded. Chi-square tests were used to compare responses between the groups. Results: Trainee physicians were more likely than attending physicians to agree that treating OUD with medication is more effective than treatment without medication (76 % versus 67 %, p = 0.03). Half of trainee physicians (51 %) expressed interest in treating patients with OUD compared to 20 % of attending physicians. Trainee physicians expressed greater support than attending physicians for policies that loosen restrictions on prescribing OUD medications. Conclusions: Relative to attending physicians, the emerging cohort of primary care physicians may be more receptive to working with patients with OUD and prescribing medication. Enhancing medical training on OUD and its treatment, exposing clinicians to individuals in recovery from OUD, and increasing support for clinicians that provide medication treatment for OUD may strengthen this group's capacity to respond to the opioid crisis.